2013
DOI: 10.4161/rdis.25212
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime risk estimators in epidemiological studies of Krabbe Disease

Abstract: This review addresses difficulties arising in estimating epidemiological parameters of leukodystrophies and lysosomal storage disorders, with special focus on Krabbe disease. Although multiple epidemiological studies of Krabbe disease have been published, these studies are difficult to reconcile since they have used different study populations and varying methods of calculation. Confusion exists regarding which epidemiological parameters have been estimated; the current review shows that most previous estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
1
28
1
2
Order By: Relevance
“…As pointed out by Foss et al and by Vanderver et al it is difficult to find other valid epidemiological data to compare with those reported in this paper. In 1997 Heim et al reported the results of a national survey of ‘all relevant medical institutions’ in Germany.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…As pointed out by Foss et al and by Vanderver et al it is difficult to find other valid epidemiological data to compare with those reported in this paper. In 1997 Heim et al reported the results of a national survey of ‘all relevant medical institutions’ in Germany.…”
Section: Discussioncontrasting
confidence: 51%
“…They decided that it was best to calculate the 'lifetime These can all be considered as peroxisomal biogenesis disorders, making a sub-group of 7+6+5=18 cases. Birth-68mo As pointed out by Foss et al 6 and by Vanderver et al 1 it is difficult to find other valid epidemiological data to compare with those reported in this paper. In 1997 Heim et al 15 reported the results of a national survey of 'all relevant medical institutions' in Germany.…”
Section: Calculation Of Lifetime Risk and Comparison With Other Epidementioning
confidence: 53%
“…Its estimated overall prevalence is 1:100,000 births, while a very high prevalence is found in two separate inbred Druze and Arab Muslim communities in Israel (Foss et al 2013;Rafi et al 1996). Its estimated overall prevalence is 1:100,000 births, while a very high prevalence is found in two separate inbred Druze and Arab Muslim communities in Israel (Foss et al 2013;Rafi et al 1996).…”
Section: Results: To -Discussionmentioning
confidence: 98%
“…Its estimated overall prevalence is 1:100,000 births, while a very high prevalence is found in two separate inbred Druze and Arab Muslim communities in Israel (Foss et al 2013;Rafi et al 1996). Assuming a birth rate of 100,000/year, a rough incidence estimate for Krabbe disease in Greece would be 0.63/ 100,000 births.…”
Section: Results: To -Discussionmentioning
confidence: 99%